CERCETĂRI PRIVIND CALITĂŢILE UNOR MOMELI ALIMENTARE ÎN SCOPUL UTILIZĂRII LOR ÎN TRASAREA CURBEI DE ZBOR A SPECIEI SYNANTHEDON MYOPAEFORMIS (BORKHAUSEN, 1789) - Georgeta Orban; I. Oltean; Teodora Florian (Agricultura, 2010)
Research on quality for food baits for their use in drawing the flight curve of special Synanthedon Mynanthedon specie. Species Synanthedon myopaeformis Borkhausen show many bioecological features: biological cycle varies depending on geographic area, prolonged flight activity of adults, the prevalence of endophyte life of the total biological cycle, which raises difficulties in tracking individuals on the same sequence of stages of development, significant variability degree of development of larvae, growth impossible in the laboratory environment, synthetic and / or semi synthetic, the difficulty of observation and capture of adults by mechanical and physical means. Because of these difficulties worldwide species is relatively little known among the various authors and there are discrepancies relating to knowledge of their bioecology. For drawing the flight curve, in the province of Saragossa Spain have used food traps consist of diluted juice of apples or pears determination that adults are present from May until July, and maximum flight curve is reached in June (CABEZUELO-PERZ P. et al, 1972). In Germany, used to combat pests Synanthedon myopaeformis Borkhausen a juice prepared from 11 liters of vinegar, 11 liters of apple juice, 100 g sugar and 8 liters of water. This mixture was placed in containers tall, half-filled at the beginning of the flight (late May - early June). Equally effective is water and boiled with the juice of apples damaged (G Probst, 1988; M. BURKE et al, 1999).